If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 = -10x + 43 Reorder the terms: -7 = 43 + -10x Solving -7 = 43 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -7 + 10x = 43 + -10x + 10x Combine like terms: -10x + 10x = 0 -7 + 10x = 43 + 0 -7 + 10x = 43 Add '7' to each side of the equation. -7 + 7 + 10x = 43 + 7 Combine like terms: -7 + 7 = 0 0 + 10x = 43 + 7 10x = 43 + 7 Combine like terms: 43 + 7 = 50 10x = 50 Divide each side by '10'. x = 5 Simplifying x = 5
| y^6-5=4 | | 6000=x/3 | | 21/2*36/7 | | z/2+3/2=-10z/7-7/7+9z/4 | | -7=-x-3 | | 4(1b-3)=72 | | 21/10n=1/6 | | y^3-6=3 | | (4x)/3-2=2x | | 6x+3y-4(6x-7y)= | | 63/5-21/4 | | -6z/8+7/8=6z/5-11/5-2z/3 | | 7/3x+1/3x=2x+3/3+5/3x | | x^3+2x^2+8x+8=0 | | 2x/3-2/3=-7x/2+4x/3 | | 15.96+2s=T | | y=-3x-69 | | (x+10)/2=7(x-1) | | T=2s+25.96 | | x+2y=-18 | | .5q=315 | | -2=-2(3x-5) | | 1.9y-1.6y= | | -2x-3y=1 | | 5q=315 | | y^11+6=-7 | | 2+2x=4x-8 | | -4x-12y=36 | | y^3+5=-7 | | -16t^2-11t+150=0 | | 3x-12y=27 | | -5(-3q+11)+4(-1-5q)= |